The Limitations of FDA Criteria: Inconsistencies with Clinical Practice, Findings, and Adult Criteria as a Barrier to Pediatric Implantation - Park, Lisa R.; Gagnon, Erika B.; Brown, Kevin D. (Seminars in Hearing, 2021)
Children require greater access to sound than adults as they are learning to communicate using hearing and spoken language. Yet when it comes to cochlear implant candidacy, currently approved Food and Drug Administration (FDA) criteria for adults are much less restrictive than those for children, allowing for greater levels of residual hearing and aided speech recognition in adults. Cochlear implant guidelines for children have changed very little in the 30 years since cochlear implants have been approved for pediatrics, and this lack of change has proven to be a barrier to implantation. Using evidence-based practice, centers have been providing off-label implantation for children who fall outside of current FDA criteria, including children with more residual hearing, children with single-side deafness younger than 5 years, and infants with bilateral profound loss younger than 9 months. The purpose of this article is to outline how these restrictions impede access to implants for children and describe the evidence supporting cochlear implantation in children who fall outside of current criteria.
Keywords: children; cochlear implant; criteria; indications